2010
DOI: 10.1002/ajmg.a.33229
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of a patient with a partial trisomy 16q including the fat mass and obesity associated gene (FTO): Fine mapping and FTO gene expression study

Abstract: A female patient with a partial trisomy 16q was described previously. Her clinical characteristics included obesity, severe anisomastia, moderate to severe mental retardation, attention deficit hyperactivity disorder, dysmorphic facies, and contractions of the small joints. In this paper, we describe a more detailed analysis of the genetic anomaly in this patient. We were particularly interested in the involvement of the fat mass and obesity associated gene (FTO) in her duplication. Single nucleotide polymorph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 34 publications
1
14
0
Order By: Relevance
“…Homozygous loss-of-function of FTO was reported to cause severe growth retardation and multiple malformations, 6 whereas a duplication of FTO was found to be associated with morbid obesity. 7 Fto-knockout mice 8 and mice with a missense mutation in exon 6 9 showed leanness, postnatal growth retardation and a higher metabolic rate. Mice with one or two additional copies of Fto had a gene-dosage-dependent increase in body weight.…”
Section: Introductionmentioning
confidence: 99%
“…Homozygous loss-of-function of FTO was reported to cause severe growth retardation and multiple malformations, 6 whereas a duplication of FTO was found to be associated with morbid obesity. 7 Fto-knockout mice 8 and mice with a missense mutation in exon 6 9 showed leanness, postnatal growth retardation and a higher metabolic rate. Mice with one or two additional copies of Fto had a gene-dosage-dependent increase in body weight.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in a recent report, a subject with an 11.45 Mb duplication on chromosome 16q, including the entire FTO locus, did not exhibit altered expression of FTO. 13 Although allele specific expression analysis of five individuals demonstrated that the obesity associated SNPs in intron 1 of FTO were associated with increased FTO expression in blood, 12 other studies revealed no effect of these SNPs on FTO expression in muscle or adipose tissues. 31 This suggest that the effects of common intronic SNPs in FTO on susceptibility to obesity may be mediated in part by altered expression of other genes in the region.…”
Section: Discussionmentioning
confidence: 98%
“…However, in subjects with proximal 16q duplications, including FTO, obesity is a common but not an inevitable feature in the background of significant psychomotor and intellectual deficits. 13 We therefore sought to determine whether rare copy-number variants (CNVs) (o1%) at the FTO locus are found in subjects at the extremes of the body weight distribution, and if so, to characterize the effect of those CNVs. We identified a single large CNV spanning the FTO risk locus and characterized its molecular effects, as well as the clinical features of the subject and affected family members.…”
Section: Introductionmentioning
confidence: 99%
“…Every chromosome except chromosome number 13 was found to be reported with structural anomalies (i.e., deletions, duplications) and related to obesity. These include chromosome 1 with a recognized 1p36 deletion obesity syndrome [45]; chromosome 6 with a 6q16.2 deletion involving SIM1 gene [46]; chromosome 11 with 11p deletions involving the BDNF gene [47]; chromosome 15 with the 15q11-q13 deletion seen in Prader-Willi syndrome [25]; chromosome 16 with 16p11.2 deletions involving the SH2B1 gene [25,26] and 16q11.2 duplications involving the FTO gene [48]; chromosome 18 with 18q deletions involving the MC4R gene [49]; chromosome 20 with 20q deletions seen in Albright hereditary osteodystrophy involving the complex GNAS1 gene locus [50]; chromosome 22 with the 22q11.2 deletion seen in DiGeorge syndrome [51]; and chromosome X with a Xq27 deletion involving the FMR1 gene seen in fragile X syndrome [52]. These multiple chromosome abnormalities support the polygenic nature of obesity useful for the identification of candidate genes and their location for more precise genetic characterization and testing.…”
Section: Yrbm Znf483mentioning
confidence: 99%